The CTSimU software toolbox for CT-related image processing and quality assessment - Plotzki, David; Hartlaub, Bendix; Borges de Oliveira, Fabrício; Reuter, Tamara; Wohlgemuth, Florian; Bellon, Carsten; Hausotte, Tino (11th Conference on Industrial Computed Tomography (iCT) 2022, 8-11 Feb, Wels, Austria (iCT 2022), 2022)
A software toolbox is introduced that addresses several needs common to computed tomography (CT). Built for the WIPANO CTSimU project [1] to serve as the reference implementation for its image processing and evaluation tasks, it provides a Python 3 interface that is adaptable to many conceivable applications. Foremost, the toolbox features a pipeline architecture for sequential 2D image processing tasks, such as flat field corrections and image binning, and enables the user to create their own processing modules. Beyond that, it provides means to measure line profiles and image quality assessment algorithms to calculate modulation transfer functions (MTF) or to determine the interpolated basic spatial resolution (iSRb) using a duplex wire image [2]. It can also be used to calculate projection matrices for the reconstruction of scans with arbitrary industrial CT geometries and trajectories. The CTSimU project defined a framework of projection- and volume-based test scenarios [3] for the qualification of radiographic simulation software towards its use in dimensional metrology. The toolbox implements the necessary evaluation routines and generates reports for all projection-based tests. <br